114k views
1 vote
The point (2,6) lies on the graph of the equation y = kx^2 - 3x Find the value of K

User StackMonk
by
5.1k points

1 Answer

1 vote

Answer:

k = 3

Explanation:

y = kx² - 3x

Since the points lie on the graph we can substitute the values of x and y that's

( 2 ,6) into the equation to find k.

We have

6 = (2)²k - 3(2)

6 = 4k - 6

4k = 6 + 6

4k = 12

Divide both sides by k

That's


(4k)/(4) = (12)/(4)

We have the final answer as

k = 3

Hope this helps you

User Ddoughty
by
5.0k points